AI for the sustainable development goals - Sætra, Henrik Skaug (AI for everything, 2022)
What is artificial intelligence? What are the Sustainable Development Goals (SDGs)? How does AI affect the SDGs? Artificial Intelligence has a real impact on our lives and on our environment, and the Sustainable Development Goals enable us to evaluate these impacts in a systematic manner. This book shows that doing so requires us to understand the context of AI - the infrastructure it is built on, who develops it, who owns it, who has access to it, who uses it, and what it is used for - rather than relying on an isolationist theory of technology. By doing so, we can analyze not only the direct effects of AI on sustainability, but also the indirect - or second-order - effects. AI for the Sustainable Development Goals shows how AI potentially affects all SDGs - both positively and negatively.